The Effect of Density on Crime: Evidence from Indonesia - Grasia Veranita; Muhammad Halley Yudhistira (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
This study aims to contribute to the literature on economic density by finding empirical evidence on whether the effects of density are going higher to affect the crime rate at the district level from 2007-2018 with 440 districts. This study used crime rate as a dependent variable and population density as an independent variable also had average age, married, the proportion of divorce, the proportion of gender, and the proportion of urban as relevant variable control. Density appears to have a small effect on crime rates. The regression result using a fixed effect panel concluded the economic density has a negative association with the probability of becoming a victim of crime. Density positively impacts the environment in terms of crime prevention. The denser an area is correlated, the lower the number of victims of crimes.